The effects of the Spanish Civil War in the lives of women and children: teaching philosophy and unit plan - Chevalier, Elizabeth (Kansas State University, 2015)
The purpose of this report is to demonstrate mastery of content in the Spanish MA program in Second Language Acquisition at Kansas State University. After graduation from this program, I plan to pursue a career as a high school Spanish teacher. As evidence of content mastery, this report contains my philosophy of education, which emphasizes communicative competence in the Spanish classroom. I discuss best teaching practices in presenting and practicing Spanish vocabulary and grammar with students. The use of the target language and the integration of culture and the four language skills is designed to further my students’ development through the progression of the lesson plan, from warm-up, to input, to the activity sequence, to closure. This report also contains a rationale, or how my philosophy of education directly and specifically applies to my teaching, for a unit plan including daily lessons and related appendices on the subject of the Spanish Civil War, and outlines student learning outcomes for this unit, such as the ability to compare their home culture to the culture of the second language as well as the ability to relate art and literature to the events of the war. The topic of my unit plan is of particular interest to my students and me as wars and violence are a present reality in our world. The secondary focus of my unit plan involves the significant detrimental effects of the Spanish Civil War and well as its specific consequences in the lives of women and children.
Keywords: Spanish Civil War; Teaching philosophy; Spanish; Secondary education; Unit plan; Women and children; Foreign Language Instruction (0444); Philosophy of Education (0998); Secondary Education (0533)